NMDA and AMPA receptors contribute similarly to temporal processing in mammalian retinal ganglion cells. (15th October 2014) - Stafford, Benjamin K.; Manookin, Michael B.; Singer, Joshua H.; Demb, Jonathan B.
Abstract : Key points: In most areas of the brain, NMDA‐type glutamate receptors (NMDARs) exhibit slower kinetics than do AMPA‐type receptors (AMPARs). Most retinal ganglion cells express a combination of AMPARs and NMDARs, but whether NMDAR kinetics limit temporal encoding of light stimulation is not well understood. In this study, we measured AMPAR‐ and NMDAR‐mediated conductances evoked by visual stimulation in two types of guinea pig retinal ganglion cell. In both cell types, AMPAR‐ and NMDAR‐mediated responses encoded rapidly varying contrast modulation within the physiological range (up to 18 temporal cycles s –1 ). In retinal ganglion cells, NMDARs and AMPARs act together to encode a wide range of temporal frequencies, suggesting that NMDARs in some sensory neurons have relatively fast kinetics. Abstract: Postsynaptic AMPA‐ and NMDA‐type glutamate receptors (AMPARs, NMDARs) are commonly expressed at the same synapses. AMPARs are thought to mediate the majority of fast excitatory neurotransmission whereas NMDARs, with their relatively slower kinetics and higher Ca 2+ permeability, are thought to mediate synaptic plasticity, especially in neural circuits devoted to learning and memory. In sensory neurons, however, the roles of AMPARs and NMDARs are less well understood. Here, we tested in the in vitro guinea pig retina whether AMPARs and NMDARs differentially support temporal contrast encoding by two ganglion cell types. In both OFF Alpha and Delta ganglion cells, contrast stimulation evoked an NMDAR‐mediated response with a characteristic J‐shaped I–V relationship. In OFF Delta cells, AMPAR‐ and NMDAR‐mediated responses could be modulated at low frequencies but were suppressed during 10 Hz stimulation, when responses were instead shaped by synaptic inhibition. With inhibition blocked, both AMPAR‐ and NMDAR‐mediated responses could be modulated at 10 Hz, indicating that NMDAR kinetics do not limit temporal encoding. In OFF Alpha cells, NMDAR‐mediated responses followed stimuli at frequencies up to ∼18 Hz. In both cell types, NMDAR‐mediated responses to contrast modulation at 9–18 Hz showed delays of <10 ms relative to AMPAR‐mediated responses. Thus, NMDARs combine with AMPARs to encode rapidly modulated glutamate release, and NMDAR kinetics do not limit temporal coding by OFF Alpha and Delta ganglion cells substantially. Furthermore, glutamatergic transmission is differentially regulated across bipolar cell pathways: in some, release is suppressed at high temporal frequencies by presynaptic inhibition.